A Weavable and Scalable Cotton‐Yarn‐Based Battery Activated by Human Sweat for Textile Electronics (Adv. Sci. 7/2022). Issue 7 (4th March 2022) - Xiao, Gang; Ju, Jun; Lu, Hao; Shi, Xuemei; Wang, Xin; Wang, Wei; Xia, Qingyou; Zhou, Guangdong; Sun, Wei; Li, Chang Ming; Qiao, Yan; Lu, Zhisong
Abstract : Yarn‐Based Sweat‐Activated Batteries In article number 2103822, Yan Qiao, Zhisong Lu, and co‐workers develop a weavable, washable and scalable cotton‐yarn‐based sweat‐activated battery with a segmented structure. The 1‐dimensional design enables the battery to be integrated into fabrics as a biocompatible and reliable power source for the construction of self‐powered textile‐based wearable systems.